Computational investigations of HIV-1 protease and protease inhibitors interactions - Sham, Hoi Fung (2014)
The Human Immunodeficiency Virus (HIV) is a retrovirus that is able to replicate itself recursively in the infected. In order to stop the Human Immunodeficiency Virus (HIV) replication process, Protease Inhibitors (PIs) are introduced to inhibit the activities of the HIV protease, a major component that plays a pivotal role in the viral replication process. Studies of the interactions between the HIV protease and PIs are thus essential for effective drug design. In this project, an investigation of the interactions between the HIV type 1 (HIV-1) protease and PIs was carried out. This was done by using molecular docking of PIs with HIV-1 proteases using AutoDock Vina to predict the binding conformations of the respective docked complexes. Both wild type HIV-1 proteases and mutated HIV-1 proteases were used in the docking simulations. Analysis based on the predicted binding affinity values obtained from the docking procedures was done. It was suggested from the results that HIV-1 protease conformations as well as mutations of the HIV-1 protease could attribute to the reduction in binding affinity between the HIV-1 protease candidates and PIs. For future work, it is worthwhile to investigate the interactions between the HIV proteases and PIs using the flexible receptor docking method. Although it is computationally more expensive than rigid receptor docking that was implemented in the project, it could provide more insights to the how both the HIV proteases and PIs interact.